2004
DOI: 10.1021/la036369u
|View full text |Cite
|
Sign up to set email alerts
|

The Lotus Effect:  Superhydrophobicity and Metastability

Abstract: To learn how to mimic the Lotus effect, superhydrophobicity of a model system that resembles the Lotus leaf is theoretically discussed. Superhydrophobicity is defined by two criteria: a very high water contact angle and a very low roll-off angle. Since it is very difficult to calculate the latter for rough surfaces, it is proposed here to use the criterion of a very low wet (solid-liquid) contact area as a simple, approximate substitute for the roll-off angle criterion. It is concluded that nature employs meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
680
2
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 1,034 publications
(702 citation statements)
references
References 24 publications
14
680
2
6
Order By: Relevance
“…Consequently, easy removal of a drop from a surface requires minimization of hysteresis. In addition, it is reasonable to assume 44,116,117 that the drop will quickly react to the removing force if its actual contact area with the solid (the 'wetted area') is as small as possible.…”
Section: Surface Innovations Volume 2 Issue Si4mentioning
confidence: 99%
“…Consequently, easy removal of a drop from a surface requires minimization of hysteresis. In addition, it is reasonable to assume 44,116,117 that the drop will quickly react to the removing force if its actual contact area with the solid (the 'wetted area') is as small as possible.…”
Section: Surface Innovations Volume 2 Issue Si4mentioning
confidence: 99%
“…A drop gently deposited on the texture often is in the Cassie levitating state (33, 36), whereas after an impact it can get impaled in the so-called Wenzel state (37). Most generally, one of the states is metastable (33,34,38), with an energy barrier large enough to prevent spontaneous transition to the other state (39,40). Metastability is beneficial for achieving relatively robust slippery Cassie states (1, 2, 32, 41-44), but detrimental in strongly pinned sticky Wenzel situations (33, 45).…”
mentioning
confidence: 99%
“…The triggering mechanisms for the transition are still debated in literature [18][19][20]. Theoretical analysis [18,21,22] has shown that the state with a smaller contact angle corresponds to a lower energy level. The presence of energy barriers between the two states may prevent a spontaneous transition and triggering is needed to induce the transition from the higher energy state to the lower energy state [9,10,20,23,24].…”
Section: Cassie-baxter State Wenzel Statementioning
confidence: 99%
“…A few examples of frequently used design techniques [3,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] are listed in figure 1. Detailed descriptions of these and many more processes are given in a review by Geissler and Xia [26].…”
Section: Introduction On Patterningmentioning
confidence: 99%